PRONTOX – proton therapy to reduce acute normal tissue toxicity in locally advanced non-small-cell lung carcinomas (NSCLC): study protocol for a randomised controlled trial - Zschaeck, Sebastian (Trials, 2016)
BACKGROUND: Primary radiochemotherapy with photons is the standard treatment for locally advanced-stage non-small cell lung cancer (NSCLC) patients. Acute radiation-induced side effects such as oesophagitis and radiation pneumonitis limit patients’ quality of life, and the latter can be potentially life-threatening. Due to its distinct physical characteristics, proton therapy enables better sparing of normal tissues, which is supposed to translate into a reduction of radiation-induced side effects. METHODS/DESIGN: This is a single-centre, prospective, randomised controlled, phase II clinical trial to compare photon to proton radiotherapy up to 66 Gy (RBE) with concomitant standard chemotherapy in patients with locally advanced-stage NSCLC. Patients will be allocated in a 1:1 ratio to photon or proton therapy, and treatment will be delivered slightly accelerated with six fractions of 2 Gy (RBE) per week. DISCUSSION: The overall aim of the study is to show a decrease of early and intermediate radiation-induced toxicity using proton therapy. For the primary endpoint of the study we postulate a decrease of radiation-induced side effects (oesophagitis and pneumonitis grade II or higher) from 39 to 12%. Secondary endpoints are locoregional and distant failure, overall survival and late side effects. TRIAL REGISTRATION: Registered at ClinicalTrials.gov with Identifier NCT02731001 on 1 April 2016. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13063-016-1679-4) contains supplementary material, which is available to authorized users.